2018
DOI: 10.1108/edi-12-2017-0272
|View full text |Cite
|
Sign up to set email alerts
|

The hegemonic gender order in politics

Abstract: Despite the ongoing increase of women in the top positions, they are still underrepresented in politics. The studies focused principally on women's underrepresentation in politics neglecting the role of gender as a category that structures and makes sense of social practices. The principal aim of this study is to investigate the mechanisms that regulate the contemporary gender order in politics through discourse analysis and the contribution of the critical feminist perspective. Design/methodology/approach The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…More broadly, it is worth noting that all of this takes place in a complex framework characterized by the persistence of forces and factors that constitute a significant obstacle to women's active participation in society. The hindrance of women from the public arena is reflected in a series of complex dynamics, often rooted in gender biases, social expectations, and systemic disparities (De Simone et al 2018;Pacilli et al 2012). It is realized that this discussion not only impacts the evolution of Italian politics but also constitutes a significant contribution to the current global debate on representation and inclusion in the political sphere.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…More broadly, it is worth noting that all of this takes place in a complex framework characterized by the persistence of forces and factors that constitute a significant obstacle to women's active participation in society. The hindrance of women from the public arena is reflected in a series of complex dynamics, often rooted in gender biases, social expectations, and systemic disparities (De Simone et al 2018;Pacilli et al 2012). It is realized that this discussion not only impacts the evolution of Italian politics but also constitutes a significant contribution to the current global debate on representation and inclusion in the political sphere.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The individual in a leadership position is high on self-confidence, achievement, and dominance, and society relates these characteristics with a male role more (Kelly 1983;Rosenwasser and Dean 1989). In an Italian study on fifteen men and an equal number of women, it was found that men are mostly involved in employment in the public sphere, whereas women are more in family chores, and this gender hierarchy defines the boundaries of symbolic behaviours and objects associated with masculinity and femininity (De Simone et al 2018). Females trying to establish themselves in the market are forced to position themselves as contenders against their male counterparts and must play the game with the mindset of not perishing out in the rules set by society (Kanze et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These deeply rooted assumptions might explain some of the main obstacles to women's participation in decision-making roles, in politics and organisations that generally prevail over women's competences and abilities. This is also echoed in parental policies and their impact on mothers' employment choices (de Simone et al, 2018). According to Istat (2019), 11% of Italian women with a child has never worked since the birth of their child (as compared to an EU average of 3.7%), with regional differences strongly emerging (1 out of 5 women in the south of Italy declares to have never worked post maternity).…”
Section: Reflections: a Future For Italy After The Pandemicmentioning
confidence: 99%